Biodegradable hyaluronic acid-based triboelectric nanogenerator as self-powered temperature sensor - Candido, Iuri C.M. (2023)
Bio-based energy harvesting devices must make use of building blocks that incorporate intrinsic properties of flexibility, transparency, mechanical resistance and potential to harvest energy in contact with the body. The use of hyaluronic acid film as a tribopositive layer represents a promising strategy in bioelectronics for the development of battery-free devices. Herein, it is reported a new triboelectric nanogenerator based on the hyaluronic acid film with promising electrical output (voltage of 398.5 V and current of 21.9 μA) with a linear variation in the open circuit voltage as a function of the temperature that was explored in a prototype of a self-powered temperature sensor applied in the range of the 27 °C – 43 °C.